Innovative approaches to optimizing the road safety monitoring system - Shevtsova A.G.; Bychkova C.A.; Podkopaev A.V.; Nechaev O.Y. (BIO Web of Conferences)
The article presents a statistical analysis of innovative approaches to optimizing the system for monitoring the level of accidents and social risk, which is aimed at improving the predictive capabilities of the existing system for monitoring road safety indicators on the State Traffic Safety Inspectorate website. The purpose of this study in the field of studying the dependence of the number of social risk and road accidents is a quantitative increase in this kind of accidents on the road network in the Federal Districts. Based on the data obtained, through the use of innovative methods and calculations of social risk, such as artificial intelligence and big data analysis for constructing a safer and more optimal road safety control system. The results of the intellectual research in the field of road safety in the Federal Districts of Russia under consideration allow us to conclude that there are significant opportunities in the work of innovative approaches in the field of ensuring road safety through the introduction of intelligent systems and effective algorithms.